Community education project leadership and organizational culture: Perceptions of empowerment in an Egyptian NGO - Khairat, Aisha (AUC Knowledge Fountain, 2018)
Community education in the Arab Republic of Egypt is a model that provides education to remote, underprivileged villages and hamlets where children have no access to public education. The Community Education model is based on the philosophy of transforming individuals to reach their full potential and on instilling the seeds of empowerment and citizenship to induce societal transformation. This research aims at investigating the degree to which the leadership style and organizational culture of the Egyptian community schools demonstrates an empowering approach. Nile Valley NGO, an Egyptian Non-Governmental Organization (NGO) leading hundreds of Egyptian community schools was studied to investigate the perceptions of empowerment amongst its leadership. This in turn will have serious implications on the level of empowerment the communities managed by Nile Valley NGO are experiencing, and will serve as an indicator to the degree to which community schools are achieving their goals in transforming individuals and empowering communities and reforming Egyptian education - and not just a tool to reach literacy. This mixed-methods research utilized surveys and semi-structured interviews to capture the perceptions of empowerment in the views of a sample of 380 community schools facilitators (teachers) spanning eight Egyptian governorates and Nile Valley NGO's Community Education project team and leadership. The findings demonstrate interesting leadership approaches with traits from transformational and servant leadership theoretical models. The organizational culture at Nile Valley NGO reflects the universal dichotomy between market-oriented and humanitarian orientations. The perceptions of empowerment were positive and several success stories were uncovered in spite of the many challenges faced on the national level and despite the scarcity or resources.